2014
DOI: 10.1016/j.jcol.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of time on the quality of life of patients with intestinal stoma

Abstract: Introduction the changes caused by ostomy are not restricted to gastrointestinal physiology, but also affect self-esteem and body image, causing changes in family, professional, social and emotional life. Objective to evaluate the quality of life in ostomized patients. Method a cross-sectional epidemiological study was carried out in individuals enrolled in the Valeparaíbana Ostomy Association. We analyzed thirty individuals divided into two equal groups according to the time of the stoma: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
20

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 7 publications
(6 reference statements)
0
10
0
20
Order By: Relevance
“…It is proposed, then, counseling people with stoma about sexual health. 29 In another study 30 more than 80% of survey participants found to be sexually active before surgery for making the stoma, only 33.3% returned to sexual activity after surgery. By associating active sex life and marital status, we obtained results noting that married individuals have a higher prevalence of sexual activity than the other groups.…”
Section: Discussionmentioning
confidence: 95%
“…It is proposed, then, counseling people with stoma about sexual health. 29 In another study 30 more than 80% of survey participants found to be sexually active before surgery for making the stoma, only 33.3% returned to sexual activity after surgery. By associating active sex life and marital status, we obtained results noting that married individuals have a higher prevalence of sexual activity than the other groups.…”
Section: Discussionmentioning
confidence: 95%
“…Podendo, inicialmente, manifestar o desejo pela morte. A atuação de uma equipe multiprofissional capaz de identificar e intervir em cada etapa, o apoio da família pode ser determinante na decisão pela vida [11][12][13] . O apoio psicológico pode contribuir para a compreensão e esclarecimento dos substratos psicológicos existentes e no auxílio da utilização de estratégias de enfrentamento mais adequadas, constituindo um desafio para os membros da equipe que presta assistência [10][11][12] .…”
Section: ] (Entrevistado C)unclassified
“…O desconhecimento de como viver com estoma e conviver na sociedade pode ser motivo de negação para ele mesmo e para os demais, sendo um importante aspecto para isolamento social 2, 13 . Tal aspecto pode dificultar o processo de aceitação, de adaptação, de autocuidado e de reabilitação, impactando naa qualidade de vida.…”
Section: ] (Entrevistado C)unclassified
See 2 more Smart Citations